2014
DOI: 10.1097/aud.0000000000000020
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Phoneme Discrimination Training in a Randomized Controlled Trial of 50- to 74-Year-Olds With Mild Hearing Loss

Abstract: Objectives:The aims of this study were to (i) evaluate the efficacy of phoneme discrimination training for hearing and cognitive abilities of adults aged 50 to 74 years with mild sensorineural hearing loss who were not users of hearing aids, and to (ii) determine participant compliance with a self-administered, computer-delivered, home- and game-based auditory training program.Design:This study was a randomized controlled trial with repeated measures and crossover design. Participants were trained and tested o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
106
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(120 citation statements)
references
References 65 publications
1
106
1
6
Order By: Relevance
“…Participants were recruited and took part in in only one study. The studies and the 102 results are described in more detail elsewhere (AT1, Ferguson et al, 2014;AT2, Henshaw & Ferguson, 2014;WMT, Henshaw & Ferguson, 2013;MES, Ferguson et al, in review Nevertheless, access to IT and mobile technologies for the over-55s is increasing, and will 161 continue to increase over the coming years (Deloitte, 2014). There was no evidence that PC …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were recruited and took part in in only one study. The studies and the 102 results are described in more detail elsewhere (AT1, Ferguson et al, 2014;AT2, Henshaw & Ferguson, 2014;WMT, Henshaw & Ferguson, 2013;MES, Ferguson et al, in review Nevertheless, access to IT and mobile technologies for the over-55s is increasing, and will 161 continue to increase over the coming years (Deloitte, 2014). There was no evidence that PC …”
mentioning
confidence: 99%
“…accessibility to healthcare (Fabry, 2010), with the added advantage of being delivered 50 remotely in patients' homes (Ferguson et al, 2014;Henshaw & Ferguson, 2013). A 51 systematic review of peer-reviewed articles concluded that tele-audiology provided the 52 potential to extend services beyond the audiology clinic, in particular to under-served 53 communities and those with poor accessibility to audiology services (Swanepoel & Hall,54 2010).…”
mentioning
confidence: 99%
“…Auditory training has been shown to transfer positively to enhanced detection of untrained stimuli and produce prolonged cognitive performance improvements (Sweetow & Sabes 2006;Ferguson, Henshaw, Clark & Moore, 2014). In a collaborative project between the University of Minnesota and Starkey Hearing Technologies, benefits of auditory training using RMQ after amplification were investigated.…”
Section: Investigation Of the Efficacy Of Readmyquipsmentioning
confidence: 99%
“…Participants in the control group engaged in active listening to books on tape and were tested later on their listening comprehension. The goal of the study was to evaluate the generalizability of training to the cognitive skill of auditory selective attention (Moore & Amitay, 2007;Green & Bavelier, 2003;Sweetow & Sabes, 2006;Ferguson et al, 2014) in individuals who were first-time hearing aid users.…”
Section: Investigation Of the Efficacy Of Readmyquipsmentioning
confidence: 99%
“…That is, despite the gains seen in the measured tasks, hearing-impaired listeners report continuing difficulty with other activities, such as listening in noise or understanding accented speech. While adjustments to the standard training may allow it to promote learning which generalizes to these areas, such generalization across tasks appears so far to be limited in scope (Loebach, Pisoni, & Svirksy, 2009; but see Ferguson, Henshaw, Clark, & Moore, 2014). …”
mentioning
confidence: 99%